Analysis of hydration patterns of elite gymnasts. Intervention to improve performance - Fernández de Landa, J.; Strunk, R.; Fernández, J.; Jiménez, S.; Palacios, N. (Archivos de medicina del deporte, 2018)
Introduction: Male artistic gymnastics is a sport practiced individually with 6 different apparatus. It is a modality of high intensity and impact. Adequate hydration is important to avoid a decrease in performance and to reduce the risk of fatigue injuries.